Implementasi Pendidikan Madrasah Diniyah dalam Penguatan Mata Pelajaran PAI di SMP Negeri Mamba’ul Falah Kedungliwung Kemiri Singojuruh Kabupaten Banyuwangi - Ahmad Hasyim Fauzan (Tarbiyatuna Kajian Pendidikan Islam, 2019)
This study aims to describe the implementation of Early Islamic Education in Middle School Manba'ul Falah Kedungliwung Kemiri Singojuruh Banyuwangi. This research is a descriptive study with a qualitative approach. The techniques carried out in the analysis of the data are display data, data reduction, and conclusion. The validity of the data is done through continuous observation, technical triangulation, and member check. The results showed that structure of Diniyah Madrasa Manba'ul Falah State Middle School contains objective religious education values. MADIN implementation in the classroom is developed through spontaneous activities, routine activities and conditioning. MADIN's educational values developed are students becoming people who are fasanah wafilakhiroti hasanah (good people in the world and good people in the hereafter).